Równania różniczkowe filtracji cieczy niejednorodnych - GRABARCZYK, Czesław (Engineering Transactions, 1966)
Differential equation of filtration of a nonhomogeneous liquidGeneral differential equation is derived, with certain assumptions, for the distribution of saturation in the transition zone during an expulsion process of a liquid by another one in a homogeneous porous body, taking into consideration the capillary pressure and the influence of gravity forces.It is shown that the equations known from the literature are particular cases of the equation derived. The general solution is reduced to the canonical form and completed with the initial and boundary conditions of the physical problem under consideration.